Ground glass opacity on chest CT scans from screening to treatment: A literature review. Issue 10 (14th July 2020) - Lin, Yi-Han; Hsu, Han-Shui
Abstract : Lung cancer is the most common cause of cancer death in the world. However, recent studies have found that patients with pulmonary ground-glass opacity (GGO) have a better prognosis. Considering its low invasiveness, sublobar resection may be an appropriate treatment of choice. Low-dose computed tomography (CT) is recommended for the high-risk groups of lung cancer. Patients with nonsolid nodule are suggested to take annual low dose CT following-up. For part-solid or solid nodules, the solid component size less or more than 8 mm is the watershed of surgical treatment. Increasing tumor size is a hint of malignancy. Biopsy can be performed for clinically highly suspected malignant nodules. The endobronchial ultrasound biopsy, CT-guide biopsy, or surgical excision are the mainstream for the diagnosis of lung nodules. But for treatment, the sublobar resection is the mainstream of pulmonary GGO. A precise localization technique makes surgeons get enough resection margin and preserve more pulmonary function of the patients. The different localization technique is suitable for different kind nodular position. For patients with pure pulmonary GGO, annual low dose CT checkup is suitable. If the tumor size or solid part of the tumors increased gradually, adequate sublobar resection after tumor localization technique may provide good prognosis and preserve more pulmonary function of the patients.